2018
DOI: 10.1371/journal.pone.0199946
|View full text |Cite
|
Sign up to set email alerts
|

The effect of HIV infection on glycaemia and renal function in type 2 diabetic patients

Abstract: BackgroundInfection with, and treatment of HIV is associated with effects on glycaemia and renal function. The purpose of this study was therefore to compare glycaemic control and albuminuria in HIV-positive and HIV-negative type 2 diabetic patients.Materials and methodsDiabetic patients with and without HIV infection were recruited from a diabetic clinic at Chris Hani Baragwanath Hospital in Soweto, South Africa. Data was collected on weight, height, HbA1c, fasting glucose, urine albumin:creatinine ratio, HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
0
17
1
Order By: Relevance
“…All reported a greater discrepancy between HbA 1c and FG in people living with HIV compared to the control group. Khoza et al 34 found people living with HIV had a higher FG, by 4.4%, but HbA 1c 2.8% lower in comparison to the control group. Slama et al 13 used multivariate median regression and found at a FG of 6.9 mmol/L (125 mg/dl) median HbA 1c were 0.21% lower in HIV‐infected men compared to HIV‐uninfected men.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…All reported a greater discrepancy between HbA 1c and FG in people living with HIV compared to the control group. Khoza et al 34 found people living with HIV had a higher FG, by 4.4%, but HbA 1c 2.8% lower in comparison to the control group. Slama et al 13 used multivariate median regression and found at a FG of 6.9 mmol/L (125 mg/dl) median HbA 1c were 0.21% lower in HIV‐infected men compared to HIV‐uninfected men.…”
Section: Resultsmentioning
confidence: 94%
“…Six studies used fasting glucose as an additional marker of glycaemia 13,34‐37 to monitor diabetes with one study 38 also using Fructosamine, five 13,34‐37 included a control cohort of participants without HIV. Four of the controlled studies compared HbA 1c and FG values.…”
Section: Resultsmentioning
confidence: 99%
“…4 Relationships have been described between BMI and glycaemic control, but no studies were found, to our knowledge, on the association between adult height and glycaemic control in PLWD. In Soweto, South Africa (SA), Khoza et al 5 assessed the effect of HIV on glycaemia and renal function in patients with T2DM; however, no mention was made of any relationship between glycaemic control and patient height. Erasmus et al 6 assessed DM and metabolic syndrome in Cape Town, but also made no mention of any associations between height and glycaemic control.…”
Section: Introductionmentioning
confidence: 99%
“…Erasmus et al 6 assessed DM and metabolic syndrome in Cape Town, but also made no mention of any associations between height and glycaemic control. Glycaemic control in PLWD and HIV (PLWDH) has been shown to be suboptimal in SA 5 . Within the PLWDH cohort this can occur in those who are antiretroviral therapy (ART) naive, those on ART, as well as in those with a cluster of differentiation (CD4) level < 200 cell/μl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation